Impact of Artificial Intelligence on Undergraduate Mathematical Creativity and Problem-Solving Skills - Dahal , Prem Prasad (Academic Journal of Mathematics Education, 2025)
Artificial intelligence (AI) is also making a difference in education in mathematics, particularly in creativity and problem-solving skills. This research aimed to examine the impact of the familiarity of Artificial Intelligence (AI) on mathematical creativity and problem-solving skills of undergraduate students in Kathmandu Valley, Nepal. A convergent mixed methods design was adopted in which there were 250 undergraduate students. Quantitative data was collected using an adapted structured questionnaire containing Likert scale items and qualitative data was obtained from the open-ended data in a structured questionnaire. Quantitative data were analyzed using the methods of descriptive statistics, Pearson correlation, multiple regression, and independent samples t-test and qualitative data using the methods of thematic analysis. The results revealed strong and significant positive relationships between the AI familiar, creativity and problem-solving skills. Regression analysis showed that the AI familiarity and creativity successfully predicted problem-solving performance significantly (R2 = 0.828, p < .001). Gender differences were also present having higher problem-solving scores for the female students. Qualitative results found that students considered AI as a cognitive support tool which supported exploratory thinking and flexibility in finding solutions, although it was understood that the over-reliance and misuse of AI for ethics purpose were raised. The conclusion of the study is that AI has an enormous potential to develop higher order thinking in mathematics, provided the integration of AI is responsible. The results suggested the importance of the need for organized AI literacy initiatives and clear institutional guidelines to provide balanced and ethical implementation within the higher education domain.